Evaluation of the toxicological screening limit and threshold of toxicological concern in medical device toxicological risk assessment for various patient populations - Shaoping Wu; Jared Wilsey; Matt Lewis; Mao-wen Weng; Yayi Swain; Joelle Hakimi; Junia Pereira; Xiaoling (Sharlene) Dai; Echoleah S. Rufer; Scott Citrowske; Robert Shulfer; Marika Kamberi (Regulatory Toxicology and Pharmacology, 2026)

Oral administration of dopamine boosts anti-Vibrio immunity in shrimp through Dorsal pathway activation - Zi-ang Wang; Shun Liu; Zexu Zhao; Xiaojia Liao; Linwei Yang; Hongliang Zuo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2026)

Biocontrol for Shrimp Disease: Comprehensive Review and a Bacterial Disease Biocontrol Practice - Xinyi He; Jian He; Minghong Liu; Menghuang Xu; Jianjun Jiang; Minze Liao; Chengcheng Wu; Peiyun Han; Long Zhang; Shaoping Weng; Zhixun Guo; Jianguo He (Reviews in Aquaculture, 2026)
Biocontrol is a key strategy for disease control, as it is environmentally friendly and widely applicable. This review elaborates on biocontrol in aquaculture, particularly in shrimp culture. Biocontrol in shrimp culture mainly relies on four strategies: (i) direct kill pathogen by Bdellovibrio or bacteriophages; (ii) suppression of intestinal pathogens with probiotics; (iii) reduction of environmental pathogens via probiotics, biofloc, or bivalves and fish; and (iv) blocking transmission of pathogens using predatory fish. “Shrimp‐fish polyculture” system for diseased biocontrol, which is convenient, effective, and affordable, focuses on blocking disease transmission routes. The efficacy of this strategy has been firmly established for white spot syndrome virus (WSSV). However, its application to other shrimp diseases is not widespread. Herein, a “shrimp‐fish polyculture” biocontrol plan was designed and successfully validated against Vibrio harveyi in shrimp. These findings successfully expand the application of the “shrimp‐fish polyculture” system to the control of bacterial diseases in shrimp, thereby offering new perspectives and methods for the biocontrol of diseases caused by various shrimp pathogens.

Recycling and valorization of waste colored polyester through a zero-waste approach - Yazhou Wang; Shuhua Wang; Ji Lan; Shaoping Jiang; Yufang Weng; Sheng Shi; Chengyong Gao; Meiling Zhang (Waste Management, 2026)

Exploration of a framework to identify cohort of concern substances in medical device risk assessment - Mao-wen Weng; Xiaoling (Sharlene) Dai; Shaoping Wu; Jared Wilsey; Matt Lewis; Robert F. Shulfer; Marika Kamberi (Regulatory Toxicology and Pharmacology, 2026)

Integrin α5 is involved in immune defense by regulating hemocyte phagocytosis in shrimp - Lingling Li; Bangping Hu; Zi-ang Wang; Jiefeng Gao; Shaoping Weng; Jianguo He; Xiaopeng Xu; Hongliang Zuo (Fish & Shellfish Immunology, 2025)

P38 MAPK regulates phagocytosis of bacteria and fungi by hemocytes in Macrobrachium rosenbergii - Ran Geng; Bangping Hu; Alian Liao; Lingling Li; Hongliang Zuo; Zhixun Guo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2025)

Spontaneous development and characterization of an endothelial-like cell line from mandarin fish Siniperca chuatsi - Jiaming Chen; Zhong Mi; Wenfeng Zhang; Panpan Luo; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

TRIM22 in Litopenaeus vannamei activates Dorsal by accelerating Cactus's degradation to mediate antiviral immunity - Xuanzheng Di; Hao Yang; Airong Lv; Xiaodi Wang; Ruiying Li; Ranran Wang; Bin Yin; Sheng Wang; Shaoping Weng; Chaozheng Li; Jianguo He; Haoyang Li (Fish & Shellfish Immunology, 2025)

Scale drop disease virus (SDDV) triggers ferroptosis both in mandarin fish (Siniperca chuatsi) and MFF-1 cells to facilitate virus infection via linking to transferrin receptor 1 (TfR1) - Jiaming Chen; Yuting Fu; Shuyi Chen; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

A cytokine receptor domeless restrains mud crab reovirus infection via JAK-STAT signaling pathway in mud crab (Scylla paramamosain) - Hengwei Deng; Yetong Ke; Shaoping Weng; Lei Hu; Wenfeng Zhang; Yujia Sun; Linwei Yang; Xuewen Wang; Mingyang Feng; Weiliang Guo; Zhihong Zhong; Dongdong Zhang; et al. (Fish & Shellfish Immunology, 2025)

Dual protection against grouper Rana-Iridovirus (GIV-R) and nervous necrosis virus (NNV) by novel GIV-R-Δ51−NNV-CP chimeric vaccine candidates - Shan Ding; Yong Li; Qianqian Sun; Zhiming Zhu; Fangzhao Yu; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Acute hypoxia stress impairs Litopenaeus vannamei resistance to white spot syndrome virus by downregulating chitin-binding proteins - Honghui He; Shaoping Weng; Chaozheng Li; Jianguo He (Fish & Shellfish Immunology, 2025)

Megalocytivirus: A Review of Epidemiology, Pathogenicity, Immune Evasion, and Prevention Strategies - Changjun Guo; Jian He; Xiaopeng Xu; Shaoping Weng; Jianguo He (Reviews in Aquaculture, 2025)
Megalocytivirus, a large double‐stranded DNA virus belonging to the Iridoviridae family, has infected over 100 species of fish, leading to significant economic losses in the aquaculture, food, and ornamental fish industries. These viruses exhibit icosahedral symmetry and have diameters ranging from 120 to 200 nm. Two distinct viral species of genus Megalocytivirus have been identified: Megalocytivirus pagrus 1 and Megalocytivirus lates 1 . Megalocytivirus pagrus 1 encompasses three distinct genotypes: infectious spleen and kidney necrosis virus, red seabream iridovirus, and turbot reddish body iridovirus, whereas Megalocytivirus lates 1 comprises a single genotype, known as scale drop disease virus. Infection with Megalocytivirus pagrus 1 is a notifiable disease to the World Organisation for Animal Health. Over the past two decades, significant progress has been made in various aspects of megalocytivirus biology, including the understanding of its molecular genetics, transmission modes, host ranges, pathogenic mechanisms, diagnostic methodologies, and vaccines. This review provides a comprehensive overview of the current understanding of megalocytiviruses, focusing on its epidemiology, pathogenicity, immune evasion, and prevention strategies for fish infected with megalocytiviruses. We hope that these findings will provide new insights in the development of effective prevention and control strategies for megalocytiviral diseases.

Acute hypoxia stress decreases the resistance of Litopenaeus vannamei to Vibrio parahaemolyticus infection - Honghui He; Shaoqing Huang; Shaoping Weng; Jianguo He; Chaozheng Li (Aquaculture, 2025)

Establishment and characterization of a novel cell line derived from spotted sea bass Lateolabrax maculatus and its susceptibilities to iridoviruses - Zhipeng Zhan; Xueqian Cao; Jie Su; Yangchi Cui; Yang Zheng; Pengli Xiao; Zhoutao Lu; Shaoping Weng; Changjun Guo; Jianguo He (Aquaculture, 2025)

Ammonia nitrogen stress induces dysbiosis of the intestinal bacterial community and facilitates the enrichment of pathogenic bacteria in intestines of shrimp - Dongwei Hou; Haoyang Li; Sheng Wang; Shaoping Weng; Jianguo He (Aquaculture, 2025)

A novel perlucin with immune regulatory functions protects Litopenaeus vannamei against Vibrio parahaemolyticus infection - Zi-ang Wang; Linwei Yang; Zexu Zhao; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2024)

Environmental dispersal and host priority effect alternatively dominate intestinal microbiota succession of cultured shrimp along with host development - Dongwei Hou; Renjun Zhou; Zhixuan Deng; Shenzheng Zeng; Shaoping Weng; Jianguo He; Zhijian Huang (Marine Life Science & Technology, 2024)

Nitrite nitrogen stress disrupts the intestine bacterial community by altering host-community interactions in shrimp - Dongwei Hou; Haoyang Li; Sheng Wang; Shaoping Weng; Jianguo He (Science of The Total Environment, 2024)

Orange-spotted grouper IFNh response to NNV or MSRV and its potential antiviral activities - Siyou Huang; Rui Zheng; Yiling Kang; Linwei Yang; Jie Gao; Qingqing Liu; Shaoping Weng; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Basigin binds bacteria and activates Dorsal signaling to promote antibacterial defense in Penaeus vannamei - Linwei Yang; Zi-ang Wang; Yushi Gan; Hongliang Zuo; Hengwei Deng; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Development and characterization of a spleen cell line from yellowfin seabream Acanthopagrus latus and its susceptibility to Mandarinfish ranavirus - Zhipeng Zhan; Jiajie Fu; Huiquan Chen; Hongbo Pan; Shaoping Weng; Jianguo He; Changjun Guo (Journal of Fish Diseases, 2023)
Yellowfin seabream ( Acanthopagrus latus ) is one of the most commercially important marine fish in China. In this study, a new continuous cell line, named ALS cells, was developed from the spleen tissue of A. latus . The cell line was maintained in Dulbecco's modified Eagle medium/Nutrient Mixture F‐12 Ham (DMEM/F‐12) supplemented with 10% fetal bovine serum (FBS) and successfully cultured up to 50 passages. The cell line was authenticated by amplifying and sequencing mitochondrial cytochrome C oxidase subunit‐I ( coi‐I ) gene. The ALS cell line had the maximum growth rate in DMEM/F‐12 medium containing 20% FBS at 27°C. Chromosome number analysis showed that the ALS cells have a modal diploid chromosome number of 34. The ALS cell line was transfected with the pEGFP‐N1 plasmid, and green fluorescence was observed. The ALS cell line was used for testing Mandarinfish ranavirus (MRV) susceptibility, and the cytopathic effects in the cell line were observed at 4 days post‐infection (dpi). Furthermore, the susceptibility of the ALS cell line to MRV and the levels of MRV mRNA and viral loads were found to be significantly increased at 1–7 dpi. This study revealed that the ALS cell line could be useful for molecular, virological, and biotechnological studies on yellowfin seabream.

Host and transmission route of Enterocytozoon hepatopenaei (EHP) between dragonfly and shrimp - Naresh Kumar Dewangan; Jianhu Pang; Caiyuan Zhao; Changzheng Cao; Bin Yin; Shaoping Weng; Jianguo He (Aquaculture, 2023)

The Hippo-Yki pathway downstream transcription factor Scalloped negatively regulates immune defense against Vibrio parahaemolyticus infection in shrimp - Linwei Yang; Deyu Han; Zi-ang Wang; Nuo Chen; Hongliang Zuo; Zhixun Guo; Menghuang Xu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

A novel Toll receptor from Pacific white shrimp Penaeus vannamei is involved in immune defense against Vibrio parahaemolyticus infection - Shengwen Niu; Yuening Zhu; Ran Geng; Nuo Chen; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Aquaculture, 2023)

Effectively protecting Asian seabass Lates calcarifer from ISKNV-I, ISKNV-II, RSIV-II and SDDV by an inactivated ISKNV-I and SDDV bivalent vaccine - Yuting Fu; Yong Li; Wenfeng Zhang; Weixuan Fu; Wangdong Li; Zhiming Zhu; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Production and characterization of monoclonal antibodies against mandarinfish ranavirus and first identification of pyloric caecum as the major target tissue - Wenfeng Zhang; Hengwei Deng; Yuting Fu; Weixuan Fu; Shaoping Weng; Jianguo He; Chuanfu Dong (Journal of Fish Diseases, 2023)
Mandarinfish ranavirus (MRV), also known as a variant of largemouth bass virus (LMBV), is an emerging pathogen in mandarinfish aquaculture. In this study, monoclonal antibodies (mAbs) against MRV were produced and characterized, and 7 mAbs were obtained through Western blotting screening and all 7 mAbs specifically recognized MRV/LMBV but not several piscine iridoviruses as ISKNV, GIV and TFV. By LC MS/MS analysis, the recognized viral proteins by seven mAbs were identified as MRV‐pORF47L, MRV‐pORF55R, MRV‐pORF57L, MRV‐pORF77L and MRV‐pORF78L, respectively, and all five viral proteins are late expression structural proteins by Western blotting. Based on mAb 1C4, immuno‐histochemistry and immuno‐histo‐fluorescence were performed to re‐assess the tissue tropism of MRV. The result showed that abundant reactive signals were observed in infected spleen, kidney as well as intestine and pyloric caecum. Real‐time quantitative PCR also demonstrated that spleen as well as pyloric caecum and intestines are the major target tissue upon MRV infection. In infected intestines and pyloric caecum, numerous enlarged, multinucleated cells with intracytoplasmic inclusions were identified as the target cells of MRV, suggesting that MRV serves as a digestive tract pathogen to mandarinfish, which may explain why acute infection of MRV can cause the typical clinicopathology featured by severe ascites.

Iron loss and hypoxia are involved in lethal Pseudomonas plecoglossicida infections in the orange-spotted grouper Epinephelus coioides - Yujia Sun; Shaoping Weng; Binfu Xu; Chuanfu Dong; Jianguo He (Aquaculture, 2023)

Detection methods, epidemiological investigation, and host ranges of infectious precocity virus (IPV) - Caiyuan Zhao; Qijin Miu; Shanshan Liu; Dandan Zhou; Xinyi He; Jianhu Pang; Shaoping Weng; Jianguo He (Aquaculture, 2023)

A novel chitinase Chi6 with immunosuppressive activity promotes white spot syndrome virus (WSSV) infection in Penaeus vannamei - Shengwen Niu; Yuening Zhu; Ran Geng; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Rapid visual detection of Enterocytozoon hepatopenaei by recombinase polymerase amplification combined with lateral flow dipstick - Jianhu Pang; Caiyuan Zhao; Hualong Su; Zhongcheng Liu; Qiang Lu; Xinyi He; Shaoping Weng; Jianguo He (Frontiers in Marine Science, 2022)
Enterocytozoon hepatopenaei (EHP) is a high-impact pathogen in shrimp farming, causing huge economic losses to the global shrimp farming industry every year. However, current EHP detection methods are primarily based on the development of polymerase chain reaction (PCR) techniques that rely on sophisticated and expensive instruments. Consequently, a rapid, practical, and sensitive protocol for the detection of EHP is necessary. Recombinase polymerase amplification combined with a lateral flow dipstick (LFD-RPA) assay was developed using a pair of primers and nfo-probe targeting the conserved region of the spore wall protein gene. Under optimized reaction conditions, the LFD-RPA assay can detect 10 copies/μL of standard plasmid within 20 min at 40°C. Furthermore, the specificity of the LFD-RPA was also verified with other common pathogens of shrimp. Thirty-nine samples of Litopenaeus vannamei were collected in shrimp farms and detected using LFD-RPA and nested PCR. Thirty-two positive samples were detected by LFD-RPA. Compared with those of nested PCR, the diagnostic sensitivity and specificity of LFD-RPA were 100% and 100%, respectively. These results indicated the great application potential of the newly developed LFD-RPA assay for point-of-care diagnosis, epidemic surveillance, and epidemiological investigation of EHP.

Bacterial and eukaryotic community interactions might contribute to shrimp culture pond soil ecosystem at different culture stages - Renjun Zhou; Hao Wang; Dongdong Wei; Shenzheng Zeng; Dongwei Hou; Shaoping Weng; Jianguo He; Zhijian Huang (Soil Ecology Letters, 2022)

Abundant and Rare Microbial Communities Respectively Contribute to an Aquaculture Pond Ecosystem - Dongwei Hou; Renjun Zhou; Dongdong Wei; Shenzheng Zeng; Shaoping Weng; Qingyun Yan; Jianguo He; Zhijian Huang (Frontiers in Marine Science, 2022)
Unraveling the assembly mechanism is a core research topic of microbial ecology. Abundant and rare microbial communities are crucial for diversity, function and host health in a given ecosystem, but few studies focused on their assembly strategies. Here, we explored the microbial diversity of abundant and rare communities of water, shrimp intestine and sediment habitats in the shrimp cultural ponds. Our results found that the numbers of rare operational taxonomic units (OTUs) (6,003, 4,566 and 8,237 OTUs of water, intestine and sediment) was dozens of times more than abundant ones (only 199, 157 and 122 OTUs of water, intestine and sediment). The community diversity of abundant and rare microbial taxa was markedly different, as well as their taxonomic composition. Despite different diversity, similar abundance-occupancy relationship and biogeographic patterns between the abundant and rare microbial communities were observed, with much stronger obvious distance-decay relationships for rare community than abundant community. Furthermore, stochastic processes dominated the community assemblies of both abundant and rare microbial taxa, and deterministic process contributed more microbial community variation to rare taxa than abundant taxa. All the findings advance our understanding on the community assembly strategies of abundant and rare microbial taxa and prompt the contributions of abundant and rare microbial community to the aquatic ecosystems, which will improve aquaculture management strategy.

Transcriptional programs of infectious spleen and kidney necrosis virus (ISKNV) in vitro and in vivo - Jian-hui He; Lichao Huang; Zhixun Guo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2020)

Identification of infectious spleen and kidney necrosis virus (ISKNV)-encoded microRNAs - Jian-hui He; Qiong Xia; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2020)

A mitochondrial outer membrane-localized protein encoded by White spot syndrome virus - Muting Yan; Lihong Liu; Qianhui Liang; Jianhui He; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2016)

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

VP15R from infectious spleen and kidney necrosis virus is a non-muscle myosin-II-binding protein - Xiaopeng Xu; Ting Lin; Lichao Huang; Shaoping Weng; Wei Wei; Zhongsheng Li; Ling Lü; Zhijian Huang; Jianguo He (Archives of Virology, 2011)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Cloning, characterization and expression analysis of a CXCR1-like gene from mandarin fish Siniperca chuatsi - Chao Chen; Zhongsheng Li; Zhicheng Zhou; Zhixin Yin; Siu-Ming Chan; Xiao-Qiang Yu; Shaoping Weng; Jianguo He (Fish Physiology and Biochemistry, 2009)

Characterization of a membrane protein (VP001L) from infectious spleen and kidney necrosis virus (ISKNV) - Xiaopeng Xu; Jing Lu; Qingxia Lu; Hui Zhong; Shaoping Weng; Jianguo He (Virus Genes, 2008)